Study in Cationic Micellar Effect on Photogalvanics: Cetyl Pyridinium Chloride- Ethylene Diamine Tetra Acetic Acid – Safranine O System for Solar Energy Conversion and Storage - Gangotri, Prerna; Gangotri, K.M. (Journal of Technology Innovations in Renewable Energy, 2017)
The Object of the Study is to observe the enhancement on photogalvanics in presence of cationic micellar species i.e. cetyl pyridinium chloride in photogalvanic cell for solar energy conversion and storage. The photogalvanic system provides the higher values in maximum current value 225.0 µA as compare to 15.0 µA in without micellar system. The power at power point of the cell is 28.12 µW as compare to 3.00 µW and storage capacity of cationic micellar system is 25.0 min. as compare to 11.0 minutes in without micellar photogalvanic cell. The conversion efficiency and i-V characteristics of the cells have been determined and a mechanism has also been proposed for the generation of electricity in photogalvanic cells having cationic micellar species and without micellar system.